2019
DOI: 10.1029/2018tc005432
|View full text |Cite
|
Sign up to set email alerts
|

A Ca. 2.8‐Ga Plume‐Induced Intraoceanic Arc System in the Eastern North China Craton

Abstract: The conversion of Archean tectonic regimes from mantle plume to plate tectonic and the mechanism of subduction initiation are two crucial issues in the current Earth sciences. A typical komatiite‐tholeiite sequence consisting of ~2,850–2,800‐Ma komatiites and ~2,780–2,710‐Ma basaltic and andesitic to dacitic volcanic rocks is well preserved in the Archean Western Shandong terrane of the eastern North China Craton. These volcanic rocks were derived from the partial melting of a depleted mantle source with subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 135 publications
(221 reference statements)
0
18
0
Order By: Relevance
“…On the other hand, the mantle cooling also promote lithosphere strengthening. Integrated with petrological and structural data for a corresponding change through this interval from komatiite to calc-alkaline volcanic rock, and a changing structural style from extension to compression 26 , these newly obtained data indicate that plate tectonics were already a dominant geodynamic mechanism in the Neoarchean. However, the style of Archean plate tectonics (for example, subduction rate and subducted angle of oceanic slab) in North China may have been different from that of modern day cold plate tectonics due to its slightly higher mantle temperature on the basis of the thermomechanical numerical modeling results, and is often referred to as "hot subduction" 38,39 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, the mantle cooling also promote lithosphere strengthening. Integrated with petrological and structural data for a corresponding change through this interval from komatiite to calc-alkaline volcanic rock, and a changing structural style from extension to compression 26 , these newly obtained data indicate that plate tectonics were already a dominant geodynamic mechanism in the Neoarchean. However, the style of Archean plate tectonics (for example, subduction rate and subducted angle of oceanic slab) in North China may have been different from that of modern day cold plate tectonics due to its slightly higher mantle temperature on the basis of the thermomechanical numerical modeling results, and is often referred to as "hot subduction" 38,39 .…”
Section: Discussionmentioning
confidence: 73%
“…Recent investigations suggest that the magmatic precursors of the TTG gneisses may be derived from (1) fractionation of primary basaltic or dioritic magmas (namely, "crystal mush model") 19-21 ; (2) partial melting of hydrated mafic rocks at the base of the Earth's crust 22,23 ; or, (3) partial melting of fluid fluxed mantle (namely, "slab melting model") [24][25][26] . The most prominent features of TTG melts derived from partial melting of thickened lower crust are lower MgO content (generally less than 2.0 wt.%) and transition elements of Cr, Ni, Co and V concentrations with Mg# values (Mg# = Mg 2+ /(Mg 2+ +Total Fe 2+ ) × 100) lower than 45 based on the results of experimental petrology 27 .…”
mentioning
confidence: 99%
“…Many studies have shown that volcanic rocks with low values of LOI (<2 wt%) and Ce anomalies (δCe ratios between 0.9 and 1.1, δCe = Ce N /Sqrt (La N × Pr N )) could be designated as the least altered samples (Polat et al, 2006;Polat, Hofmann, & Rosing, 2002 S177-1 S177-3 S177-4 S177-5 S177-6 S177-7 S177-8 S177-9 S177-10 in both the rims and cores, which reflect the mobility of these elements during alteration. Accordingly, the Al 2 O 3 /TiO 2 ratio is generally considered an alteration-insensitive index and displays linear relationships with the unaltered major elements in their binary diagrams Gao, Liu, & Zhang, 2019;Guo et al, 2016;Guo, Liu, & Zhang, 2015; scatter, suggesting their mobility ( Figure 4).…”
Section: Assessment Of Elemental Mobilitymentioning
confidence: 99%
“…Both ∼2.8-2.7 and ∼2.6-2.5 Ga tectonothermal events have been identified in the WSP granite-greenstone belt (Wan et al, 2010. The ∼2.8-2.7 Ga supracrustal rocks are mainly exposed in the central part of the WSP, including the komatiite-tholeiite sequence consisting of 2,850-2,800 Ma komatiites and the~2,780-2,690 Ma basaltic and andesitic to dacitic volcanic rocks (Gao, Liu, & Zhang, 2019;Polat et al, 2006;Wan et al, 2014;Wang et al, 2013). The~2.6-2.5 Ga supracrustal rocks are mainly composed of minor mafic to felsic volcanic rocks.…”
Section: Whole-rock Sm-nd Isotopesmentioning
confidence: 99%
See 1 more Smart Citation